Graphene copper composite wire, preparation method thereof and winding
Patent Information
- Application Number
- CN202611393678.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]本申请提供一种石墨烯铜复合线材及其制备方法、及绕组,旨在解决传统铜材料性能不足的问题
[0021]本申请实施例提供的石墨烯铜复合线材包括石墨烯铜复合线芯,石墨烯铜复合线芯包括铜基体和第一石墨烯,通过将第一石墨烯引入铜基体内部,控制石墨烯铜复合线芯中第一石墨烯的面分布率≥69%,使得第一石墨烯在铜基体内分布密度高且分布均匀,实现在铜基体内部形成连续的石墨烯通道,得益于石墨烯自身优异的导热性、导电性和机械性能,使得石墨烯铜复合线材整体的导热性、导电性和机械性能得到提升;当将该石墨烯铜复合线材应用在电机的绕组中时,可以降低电机在高速运作下的趋肤效应及过热现象,大幅优化电机的效率,满足电机高转速、轻量化、降能耗的发展要求。
Smart Images

Figure CN122907415A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of conductive materials technology, specifically to a graphene-copper composite wire, its preparation method, and its winding. Background Technology
[0002] New energy vehicles, with their advantages of energy conservation, environmental protection, safety, and efficiency, have become a significant force driving the transformation of the automotive industry. As one of the three core components of new energy vehicles, the performance level of the drive motor directly determines the vehicle's power, economy, and reliability. Copper, due to its excellent electrical, thermal, and mechanical properties, has been widely used in motor windings. However, with increasing performance demands, the limitations of traditional copper materials have become a major factor hindering breakthroughs in product performance. Summary of the Invention
[0003] This application provides a graphene-copper composite wire, its preparation method, and winding, aiming to solve the problem of insufficient performance of traditional copper materials.
[0004] This application provides a graphene-copper composite wire, comprising: A graphene-copper composite wire core includes a copper matrix and a first graphene distributed inside the copper matrix, wherein the surface distribution rate of the first graphene in the graphene-copper composite wire core is ≥69%.
[0005] Optionally, in some embodiments of this application, the surface distribution of the first graphene in the single or double layer of the graphene-copper composite wire core is ≥32%; and / or, The surface distribution of the first graphene layer in the graphene-copper composite wire core is ≥25%.
[0006] Optionally, in some embodiments of this application, the single / double layer ratio of the first graphene in the graphene-copper composite wire core is ≥48%; and / or, The monolayer ratio of the first graphene in the graphene-copper composite wire core is ≥27%.
[0007] Optionally, in some embodiments of this application, the graphene copper composite core is obtained by hot pressing and sintering of graphene copper composite material, wherein the graphene copper composite material includes copper material and a second graphene attached to the surface of the copper material.
[0008] Optionally, in some embodiments of this application, in the graphene-copper composite material, the second graphene has a coating rate of ≥76% on the copper surface; and / or, The single-layer / double-layer ratio of the second graphene in the graphene-copper composite material is ≥54%; and / or, The monolayer ratio of the second graphene in the graphene-copper composite material is ≥31%; and / or, Compared with the graphene-copper composite material, the carbon loss rate of the graphene-copper composite wire core is ≤5%.
[0009] Optionally, in some embodiments of the present application, the graphene-copper composite wire further comprises a graphene layer, and the graphene layer wraps the surface of the graphene-copper composite wire core.
[0010] Optionally, in some embodiments of the present application, the carbon content in the graphene-copper composite wire is 50 ppm to 180 ppm.
[0011] Optionally, in some embodiments of the present application, the electrical conductivity of the graphene-copper composite wire is 105% IACS to 115% IACS; and / or, The thermal conductivity of the graphene-copper composite wire is ≥420 W / (m·K).
[0012] Optionally, in some embodiments of the present application, the graphene-copper composite wire further comprises an insulating layer, and the insulating layer wraps the surface of the graphene layer.
[0013] Optionally, in some embodiments of the present application, the value σ of the room-temperature electrical conductivity of the graphene-copper composite wire satisfies the following relational expression: ; In the formula, σ(Cu) is the value of the initial electrical conductivity of the pure copper matrix, and the unit of the room-temperature electrical conductivity and the initial electrical conductivity is %IACS; D is the surface distribution rate of the graphene in the first graphene-copper composite wire core, 0<D<1; F is the single-layer and double-layer rate of the first graphene in the graphene-copper composite wire core, 0<F<1; δ surface is the state value of the characteristic position of graphene on the surface layer of the graphene-copper composite wire, when the graphene-copper composite wire comprises the graphene layer, δ surface =1, when the graphene-copper composite wire does not comprise the graphene layer, δ surface = 0; α is the internal network synergistic conductivity enhancement coefficient of the graphene-copper composite wire, with a value range of 5 to 15; γ is the surface layer graphene synergistic effect factor of the graphene-copper composite wire, with a value range of 0.2 to 1.0.
[0014] Correspondingly, the present application further provides a preparation method of a graphene-copper composite wire, for preparing the aforementioned graphene-copper composite wire, comprising: growing graphene on the surface of a copper material by means of chemical vapor deposition to obtain a graphene-copper composite material; subjecting the graphene-copper composite material to hot-press sintering treatment to form a graphene-copper composite wire core, so as to obtain the graphene-copper composite wire.
[0015] Optionally, in some embodiments of this application, the chemical vapor deposition process includes a first heating stage, a reduction stage, a first growth stage, and a first cooling stage; the heating temperature of the first heating stage is 900℃~1050℃; the reduction temperature of the reduction stage is 900℃~1050℃; the growth temperature of the first growth stage is 900℃~1050℃; and the cooling rate of the first cooling stage is 10℃ / min~20℃ / min.
[0016] Optionally, in some embodiments of this application, the sintering temperature of the hot pressing sintering treatment is 700℃~900℃, the sintering pressure is 20MPa~60MPa, and the holding time is 20min~60min.
[0017] Optionally, in some embodiments of this application, the method for preparing the graphene copper composite wire further includes: coating the surface of the graphene copper composite wire core with a graphene layer.
[0018] Optionally, in some embodiments of this application, the graphene layer is coated onto the surface of the graphene-copper composite wire core using plasma-enhanced chemical vapor deposition (PECVD). The PECVD process includes a second heating stage, a cleaning stage, a second growth stage, and a second cooling stage. The heating temperature of the second heating stage is 300°C to 600°C. The temperature of the cleaning stage is 300°C to 600°C. The growth temperature of the second growth stage is 300°C to 600°C. The cooling rate of the second cooling stage is 10°C / min to 20°C / min.
[0019] Optionally, in some embodiments of this application, the method for preparing the graphene-copper composite wire before coating the graphene layer further includes: The surface of the graphene-copper composite wire core is polished.
[0020] In addition, this application also provides a winding comprising the above-mentioned graphene copper composite wire or the graphene copper composite wire prepared by the above-mentioned method.
[0021] The graphene-copper composite wire provided in this application includes a graphene-copper composite core, which comprises a copper matrix and a first graphene. By introducing the first graphene into the copper matrix and controlling the surface distribution rate of the first graphene in the graphene-copper composite core to be ≥69%, the first graphene is distributed in a high density and uniformly within the copper matrix, thus forming continuous graphene channels within the copper matrix. Thanks to the excellent thermal conductivity, electrical conductivity, and mechanical properties of graphene itself, the overall thermal conductivity, electrical conductivity, and mechanical properties of the graphene-copper composite wire are improved. When this graphene-copper composite wire is applied to the windings of a motor, it can reduce the skin effect and overheating phenomenon of the motor under high-speed operation, significantly optimize the efficiency of the motor, and meet the development requirements of high speed, lightweight, and energy-saving motors. Attached Figure Description
[0022] Figure 1 This is a cross-sectional view of the graphene-copper composite wire provided in an exemplary embodiment of this application; Figure 2 This is a longitudinal cross-sectional view of the graphene-copper composite wire provided in an exemplary embodiment of this application; Figure 3 This is a SEM image of the graphene sheets after micro-etching on the surface of the graphene-copper composite wire core in Example 1 of this application.
[0023] Explanation of reference numerals in the attached figures: 1. Graphene-copper composite core; 2. Graphene layer; 3. Insulation layer. Detailed Implementation
[0024] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0025] This application provides a graphene-copper composite wire, its preparation method, and winding. Detailed descriptions follow. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative and do not impose numerical requirements or establish an order. Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0026] This application provides a graphene-copper composite wire; please refer to [link / reference]. Figures 1-2 The graphene copper composite wire includes a graphene copper composite core 1. The graphene copper composite core 1 includes a copper matrix and first graphene distributed inside the copper matrix; the areal distribution rate of the first graphene in the graphene copper composite core 1 is ≥69%.
[0027] Graphene, a single-layer hexagonal lattice structure composed of carbon atoms, possesses excellent physicochemical properties such as high electrical conductivity, mechanical strength, and thermal stability. Graphene-copper composites, formed by combining copper and graphene, offer significant advantages in enhancing electrical conductivity. Although the combination of graphene and copper shows great promise, the preparation of high-quality graphene-copper composites requires stringent technical requirements and a systematic understanding of the performance enhancement mechanisms of graphene-copper composites.
[0028] The graphene-copper composite wire provided in this application embodiment is a linear graphene-copper composite material. The graphene-copper composite wire includes a graphene-copper composite core 1. The graphene-copper composite core 1 includes a copper matrix and a first graphene, wherein the first graphene is distributed within the copper matrix. For example, please refer to... Figure 1 and Figure 2 Inside the copper substrate, the first graphene is uniformly dispersed, thereby constructing a continuous graphene conductive network inside the copper substrate.
[0029] The surface distribution rate of the first graphene in the graphene-copper composite core 1 is ≥69%. Here, the surface distribution rate of the first graphene characterizes the spatial distribution characteristics of graphene (i.e., the first graphene) in the copper substrate in the graphene-copper composite core. It is the result of testing the graphene distribution in the graphene-copper composite core by a statistical characterization method of microscopic spatial distribution rate based on microscopic Raman lattice scanning.
[0030] The method for characterizing the surface distribution of the first graphene is as follows: The longitudinal axis of the graphene-copper composite wire core is mechanically cut to obtain the test section. After polishing the test section to remove surface impurities, the sample is tested using a micro-confocal Raman spectrometer. The core test parameters are limited as follows: the laser wavelength is 532 nm, the spot focusing diameter is <1 μm, and at least M (M≥3) spatially non-overlapping designated unit areas are randomly selected on the test section using a spatial dot matrix scanning strategy. The macroscopic size of the designated unit area is L×W (limited to a 100 μm×100 μm region in this embodiment). Using a high-precision two-dimensional electric displacement stage, a scanning path is planned in the form of a grid within the 100 μm×100 μm designated unit area. The horizontal (X-axis) step size and the vertical (Y-axis) step size are both set to 10 μm. Within a single designated unit area, a total of 10×10=100 independent micro-observation points are uniformly collected. Raman spectra were collected from each micro-observation site, and the region located at 1580±15 cm⁻¹ was extracted from the Raman spectra. -1 The intensity of the G peak at (I) G ) and located at 2700±30cm -1 2D peak intensity (I) at 2D To determine whether a test point has a "valid graphene characteristic signal", the following criteria must be met simultaneously: (1) Peak presence: in I G and I 2D Within the region, the intensity of its signal peaks is more than 3 times greater than the standard deviation of the baseline background noise (i.e., signal-to-noise ratio > 3); (2) Structural characteristics: the I G Peak and I 2D The peak intensity ratio satisfies: I 2D / I G >0.2, where I 2D / I G Sites with a value greater than 2 are identified as single-layer graphene sites, where 2 > 1. 2D / I G Sites with a value greater than 1 are identified as bilayer graphene sites, where 1 > 1. 2D / I G Points with a value >0.2 are identified as multilayer graphene points. If a test point simultaneously meets the above criteria (1) and (2), then the point is recorded as a "positive signal point"; otherwise, if a characteristic peak is missing or only the D peak of amorphous carbon (1350 cm⁻¹) is present, the point is considered a positive signal point. -1If the positive signal point is located in the vicinity of the micro-region, it is denoted as "zero signal point". The percentage of all positive signal points observed in the current micro-region by the graphene-copper composite core is defined as the surface distribution rate of the first graphene in that region.
[0031] The surface distribution of the first graphene is between 0 and 1. The closer the surface distribution of the first graphene is to 1, the higher the density and the more uniform the distribution of the first graphene within the copper matrix. Typically, in graphene-copper composite wire core 1, if the content of the first graphene is sufficient and its dispersion and distribution are good and uniform, the surface distribution of the first graphene will be closer to 1.
[0032] The graphene-copper composite wire provided in this application includes a graphene-copper composite core 1, which comprises a copper substrate and a first graphene. By introducing the first graphene into the copper substrate and controlling the surface distribution rate of the first graphene in the graphene-copper composite core 1 to be ≥69%, the first graphene is distributed in a high density and uniformly within the copper substrate, thus forming continuous graphene channels within the copper substrate. Thanks to the excellent thermal conductivity, electrical conductivity, and mechanical properties of graphene itself, the overall thermal conductivity, electrical conductivity, and mechanical properties of the graphene-copper composite wire are improved. When this graphene-copper composite wire is applied to the windings of a motor, it can reduce the skin effect and overheating phenomenon of the motor under high-speed operation, significantly optimize the efficiency of the motor, and meet the development requirements of high speed, lightweight, and energy-saving motors.
[0033] In some embodiments of this application, the surface distribution of the first graphene in the single or double layer of the graphene copper composite core 1 is ≥32%.
[0034] Graphene is mainly divided into single-layer graphene, bilayer graphene, and few-layer graphene. Single-layer graphene has one layer, which means it is a two-dimensional material composed of only one layer of hexagonal honeycomb carbon atoms. Bilayer graphene has two layers. Few-layer graphene has three to ten layers.
[0035] The number of graphene layers significantly affects its various properties. Specifically, the electrical conductivity of graphene decreases with increasing layer count, as do its tensile strength and elongation at break. The thermal conductivity of graphene exhibits a non-linear relationship with the number of layers; single-layer graphene has the highest thermal conductivity, which gradually decreases with increasing layer count, approaching the thermal conductivity level of bulk graphite after 4-5 layers. It can be seen that the lower the number of graphene layers, the better its electrical conductivity, thermal conductivity, and mechanical properties.
[0036] Single-layer and double-layer graphene refer to graphene with two or fewer layers, including single-layer and double-layer graphene. The first graphene, a single-layer and double-layer graphene, refers to both single-layer and double-layer graphene within the first graphene.
[0037] The surface distribution rate of the first graphene layer in the graphene-copper composite core 1 is ≥32%, indicating that high-density single-layer and double-layer graphene are uniformly distributed in the copper matrix of the graphene-copper composite core 1, which is beneficial to improving the conductivity, thermal conductivity and mechanical properties of the graphene-copper composite core 1.
[0038] Optionally, the surface distribution of the first graphene in the single or double layer of the graphene-copper composite core 1 is ≥32.68%.
[0039] In some embodiments of this application, the surface distribution of the first graphene layer in the graphene-copper composite core 1 is ≥25%.
[0040] Monolayer graphene has outstanding advantages in electrical conductivity, thermal conductivity, and mechanical properties. The surface distribution rate of the first layer of graphene in the graphene-copper composite wire core 1 is ≥25%, indicating that a large number of monolayer graphenes are uniformly distributed in the copper matrix of the graphene-copper composite wire core 1, which is conducive to further improving the electrical conductivity, thermal conductivity, and mechanical properties of the graphene-copper composite wire core 1.
[0041] Optionally, the surface distribution of the first graphene layer in the graphene-copper composite core 1 is ≥25.08%.
[0042] In some embodiments of this application, the single-to-double layer ratio of the first graphene in the graphene-copper composite core 1 is ≥48%.
[0043] The single-layer / double-layer ratio of the first graphene refers to the proportion of single-layer and double-layer graphene in the first graphene. In the first graphene of the graphene copper composite wire core 1, more than 48% of the first graphene is single-layer and double-layer graphene, which allows the conductivity, thermal conductivity and mechanical properties of the graphene copper composite wire core 1 to be improved simultaneously.
[0044] In some embodiments of this application, the monolayer ratio of the first graphene in the graphene-copper composite core 1 is ≥27%.
[0045] The monolayer ratio of the first graphene refers to the proportion of monolayer graphene in the first graphene. In the first graphene of the graphene copper composite wire core 1, more than 27% of the first graphene is monolayer graphene, which can further improve the conductivity, thermal conductivity and mechanical properties of the graphene copper composite wire core 1.
[0046] In some embodiments of this application, the graphene copper composite core 1 is obtained by hot pressing and sintering of graphene copper composite material, which includes copper material and second graphene attached to the surface of copper material.
[0047] The graphene-copper composite material also contains graphene, which is referred to as the second graphene for easy distinction. After hot pressing and sintering, the copper material forms the copper matrix, and the second graphene forms the first graphene. By attaching the second graphene to the surface of the copper material, the agglomeration of the second graphene can be suppressed during the hot pressing and sintering of the graphene-copper composite material into the graphene-copper composite wire core 1, thereby improving the uniformity of the dispersion of the first graphene in the copper matrix within the graphene-copper composite wire core 1.
[0048] The graphene copper composite core 1 is obtained by hot pressing and sintering graphene copper composite material. During the hot pressing and sintering process, the material is densified, and the density of the obtained graphene copper composite core 1 is improved compared with that of graphene copper composite material. The improved density of graphene copper composite core 1 will lead to the improvement of the conductivity, thermal conductivity and mechanical strength of graphene copper composite core 1.
[0049] In some embodiments of this application, in the graphene-copper composite material, the coverage rate of the second graphene on the copper surface is ≥76%.
[0050] After hot pressing and sintering, the second graphene in the graphene-copper composite material is transformed into the first graphene. The high coating rate of the second graphene on the surface of the copper material is beneficial to increasing the content of the first graphene in the graphene-copper composite core 1 on the one hand, and to inhibiting the agglomeration of the second graphene on the other hand, thereby improving the dispersion uniformity of the first graphene in the copper matrix. This dual effect ultimately improves the surface distribution rate of the first graphene in the graphene-copper composite core 1.
[0051] In some embodiments of this application, the single-to-double layer ratio of the second graphene in the graphene-copper composite material is ≥54%.
[0052] The monolayer / bilayer ratio of the second graphene refers to the proportion of monolayer and bilayer graphene in the second graphene. It can be seen that in the second graphene, at least 54 wt% of the graphene is monolayer and bilayer graphene. During the hot-pressing sintering process, although a small portion of the graphene may transform into few-layer graphene, it is still possible to ensure that at least 43 wt% of the graphene in the resulting first graphene is still monolayer and bilayer graphene.
[0053] In some embodiments of this application, the monolayer ratio of the second graphene in the graphene-copper composite material is ≥31%.
[0054] The monolayer ratio of the second graphene refers to the proportion of monolayer graphene in the second graphene. Increasing the monolayer ratio of the second graphene in the graphene-copper composite material is beneficial to increasing the monolayer ratio of the first graphene in the graphene-copper composite wire core 1.
[0055] In some embodiments of this application, the carbon loss rate of graphene copper composite core 1 is ≤5% compared to graphene copper composite material.
[0056] It is understandable that, compared to graphene-copper composite core 1, the graphene-copper composite material has a higher carbon content. During the hot-pressing sintering process, some of the second graphene in the graphene-copper composite material undergoes thermal decomposition, resulting in a lower carbon content in the formed graphene-copper composite core 1. The carbon loss rate of graphene-copper composite core 1 is the difference between the carbon content of the graphene-copper composite material and the carbon content of the graphene-copper composite core 1. A lower carbon loss rate indicates less damage to the integrity of the graphene structure in the graphene-copper composite material during the hot-pressing sintering process to form graphene-copper composite core 1.
[0057] In some embodiments of this application, the copper material includes at least one of copper powder, copper fiber, copper foam, and copper foil.
[0058] Copper powder, copper fiber, copper foam, and copper foil represent four different morphologies of copper materials. The morphology of the copper material will, to some extent, affect the distribution of the first graphene in the copper substrate in the resulting graphene-copper composite wire core 1. For an example, please refer to... Figure 1 and Figure 2 In the first type of graphene-copper composite material used for hot-pressing and sintering to form graphene-copper composite wire core 1, the copper material used is copper powder. In this case, the dispersion of the first graphene in the copper substrate is good, resulting in high electrical and thermal conductivity of the obtained graphene-copper composite wire. When the copper material is copper powder, the graphene-copper composite material is graphene-copper composite powder. As another example, in the second type of graphene-copper composite material used for hot-pressing and sintering to form graphene-copper composite wire core 1, the copper material used is copper fiber. In this case, the dispersion of the first graphene in the copper substrate is also good, but slightly worse than the first type. It was also found that the electrical and thermal conductivity of the graphene-copper composite wire is lower than that of the first type. In another example, the copper material used in the third type of graphene-copper composite material for hot-pressing and sintering to form graphene-copper composite wire core 1 is foamed copper. In this case, the dispersion of the first graphene in the copper substrate is also good, but slightly worse than the first and second types. It was also found that the electrical and thermal conductivity of the graphene-copper composite wire was lower than that of the first and second types. In yet another example, the copper material used in the fourth type of graphene-copper composite material for hot-pressing and sintering to form graphene-copper composite wire core 1 is copper foil. In this case, the first graphene is distributed in strips in the copper substrate. The results showed that the electrical and thermal conductivity of the graphene-copper composite wire was still relatively good. In preparing the graphene-copper composite wire core 1, the graphene-copper composite material using copper foil as the copper material is hot-pressed and sintered in a laminated manner. The total number of layers in the graphene-copper composite material is 100 to 300 layers.
[0059] In some embodiments of this application, the graphene copper composite wire further includes a graphene layer 2, which wraps around the surface of the graphene copper composite wire core 1.
[0060] It is understood that graphene copper composite core 1 contains graphene, and graphene layer 2 also contains graphene. For ease of distinction, the graphene in graphene copper composite core 1 is referred to as the first graphene, and the graphene in graphene layer 2 is referred to as the third graphene. It should be noted that the first graphene and the third graphene can be the same or different, and this is not limited here.
[0061] By wrapping a graphene layer 2 on the surface of the graphene-copper composite wire core 1, not only can the conductivity of the graphene-copper composite wire be improved and the local impedance growth caused by the skin effect be suppressed, but the overall heat dissipation performance (axial and radial thermal conductivity) of the graphene-copper composite wire can also be significantly optimized.
[0062] In some embodiments of this application, the main material of graphene layer 2 is third graphene, and the number of third graphene layers is 1 to 20. Optionally, the number of third graphene layers is 1 to 10. Generally, the more graphene layers there are, the closer the properties of the material are to graphite.
[0063] As an example, the third graphene may have 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 layers.
[0064] In some embodiments of this application, the ID / IG ratio of the third graphene in graphene layer 2 is 0.1 to 0.3.
[0065] ID / IG is an important parameter in Raman spectroscopy analysis of graphene, used to characterize the quality, defect level, and graphitization degree of graphene materials. The ID / IG ratio is calculated by fitting the Raman spectrum peaks and determining the area ratio (or peak intensity ratio) of the D peak to the G peak. ID (D peak intensity): located at approximately 1350 cm⁻¹. -1 The peak at this location is called the defect peak, and it is related to structural defects and disordered structures in graphene. The IG (G peak intensity) is located at approximately 1580 cm⁻¹. -1 The point at which the peak is called the G peak corresponds to the sp[a] peak of graphene. 2 The carbon atom lattice vibrations. The smaller the ID / IG ratio, the fewer the material defects and the more complete the crystal structure; the larger the ID / IG ratio, the more material defects.
[0066] The ID / IG ratio of the third graphene is 0.1~0.3, indicating that the third graphene has a high quality. The fewer defects in the graphene will make its actual performance closer to the theoretical value, and it will exhibit superior performance in terms of conductivity, mechanical strength, thermal stability and chemical stability.
[0067] As an example, the ID / IG of the third graphene is 0.1, 0.15, 0.2, 0.25 or 0.3.
[0068] In some embodiments of this application, when the surface of the graphene copper composite wire core 1 is coated with a graphene layer 2, the carbon content in the graphene copper composite wire is 50ppm to 180ppm.
[0069] The carbon content in graphene copper composite wire is 50ppm~180ppm, which can be understood as 50g~180g of carbon in 1kg of graphene copper composite wire.
[0070] The graphene-copper composite wire comprises a graphene-copper composite core 1 and a graphene layer 2. The graphene-copper composite core 1 includes a copper substrate and a first graphene layer. The first and third graphene layers are composed of carbon. The carbon content in the graphene-copper composite wire directly reflects the total content of the first and third graphene layers in the wire.
[0071] When the carbon content in graphene-copper composite wire is less than 50 ppm, the strengthening effect of graphene is not significant. However, a carbon content greater than 180 ppm leads to increased porosity and decreased density, which in turn reduces the electrical conductivity, mechanical properties, and thermal conductivity of the graphene-copper composite wire. As an example, the carbon content in the graphene-copper composite wire is any one or any two of the following values: 50 ppm, 55 ppm, 60 ppm, 65 ppm, 70 ppm, 75 ppm, 80 ppm, 85 ppm, 90 ppm, 95 ppm, 100 ppm, 105 ppm, 110 ppm, 115 ppm, 120 ppm, 125 ppm, 130 ppm, 135 ppm, 140 ppm, 145 ppm, 150 ppm, 155 ppm, 160 ppm, 165 ppm, 170 ppm, 175 ppm, and 180 ppm. Optionally, the carbon content in the graphene copper composite wire is 65ppm to 157ppm. As an example, the carbon content in the graphene copper composite wire is any one or a range between any two of 65ppm, 92ppm, 103ppm, 119ppm, 132ppm, and 157ppm.
[0072] In some embodiments of this application, the graphene copper composite wire further includes an insulating layer 3, which wraps around the surface of the graphene layer 2.
[0073] Insulation layer 3 prevents short circuits and protects the graphene-copper composite core 1 and the graphene layer 2. Optionally, the material of insulation layer 3 is an electromagnetic wire insulation material. As an example, the electromagnetic wire insulation material includes at least one of polyester varnish, polyimide (PI), polyamide-imide (PAI), insulating paper, and polyesterimide varnish. Optionally, the thickness of insulation layer 3 is 0.02 mm to 0.15 mm, for example, 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm, 0.10 mm, 0.12 mm, 0.14 mm, or 0.15 mm.
[0074] In some embodiments of this application, the conductivity of the graphene-copper composite wire is 105% IACS to 115% IACS.
[0075] IACS is a relative unit for measuring the conductivity of a material. The conductivity of annealed pure copper (Cu) at 20°C is defined as 100% IACS. It can be seen that the conductivity of the graphene-copper composite wire mentioned above is superior to that of pure copper. 100% IACS corresponds to an absolute conductivity of 58 mS / m. The conversion formula for converting the material's IACS percentage to absolute conductivity (mS / m) is: Conductivity (mS / m) = (%IACS / 100) × 58.0. When graphene-copper composite wire with high conductivity is used as a winding in motor windings, it can bring several benefits: reduced resistance loss and improved energy conversion efficiency of the motor; reduced winding temperature rise and improved motor operational reliability; and the ability to carry larger currents and increase power density.
[0076] Optionally, the conductivity of the graphene-copper composite wire is 105% IACS to 112% IACS. As an example, the conductivity of the graphene-copper composite wire is a range of any one or any two of 105.56% IACS, 107.48% IACS, 108.33% IACS, 110.21% IACS, 105.99% IACS, and 111.08% IACS.
[0077] In some embodiments of this application, the thermal conductivity of the graphene-copper composite wire is ≥420 W / (m·K).
[0078] Graphene is composed of carbon atoms arranged in sp... 2The hybrid orbitals form a single-layer two-dimensional honeycomb lattice structure, the covalent bonds between carbon atoms are extremely strong and the atoms are arranged closely, providing highly efficient channels for heat transfer. By introducing graphene inside the copper matrix and attaching graphene to the surface of the copper matrix at the same time, the heat transfer performance of the graphene-copper composite wire can be optimized, and the synergy of high electrical conductivity and high heat dissipation capacity can be achieved. When the graphene-copper composite wire is used as a winding wire in the winding of a motor, it can reduce the heat generation of the motor during high-speed operation, increase the limit rotation speed of the motor, and greatly improve the performance of the motor.
[0079] Optionally, the thermal conductivity of the graphene-copper composite wire is 422W / (m·K)~492W / (m·K), for example, any one of 422W / (m·K), 448W / (m·K), 465W / (m·K), 474W / (m·K), 434W / (m·K) and 492W / (m·K), or a range value between any two of them.
[0080] In some embodiments of the present application, the value σ of the room-temperature electrical conductivity of the graphene-copper composite wire satisfies the following relational expression: ; In the formula, σ(Cu) is the value of the initial electrical conductivity of the pure copper matrix, and the units of the room-temperature electrical conductivity and the initial electrical conductivity are both %IACS; D is the surface distribution rate of the first graphene in the graphene-copper composite core 1, 0<D<1; F is the single-to-double layer rate of the first graphene in the graphene-copper composite core 1, 0<F<1; δ surface is the characteristic position state value of the surface graphene of the graphene-copper composite wire, and when the graphene-copper composite wire includes the graphene layer 2, δ surface =1, and when the graphene-copper composite wire does not include the graphene layer 2, δ surface = 0; α is the internal network synergistic conductivity enhancement coefficient of the graphene-copper composite wire, with a value range of 5~15; γ is the surface graphene synergy factor of the graphene-copper composite wire, with a value range of 0.2~1.0.
[0081] The room-temperature electrical conductivity of the graphene-copper composite wire and the initial electrical conductivity of the pure copper matrix are both electrical conductivity at 20°C, and the units of both are %IACS. D, F, α, γ and δ surface are all unitless.
[0082] Depending on the type of the copper matrix, the value of σ(Cu) is greater than or equal to 98. Optionally, σ(Cu) is less than or equal to 103, that is, σ(Cu) is 98~103. Optionally, σ(Cu) is 98.7, then .
[0083] For example, α is a range of values between any one or any two of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and 15.
[0084] For example, γ is a range of values between any one or any two of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0.
[0085] In one example, σ(Cu) = 98.7, D = 0.97, F = 0.91, δ surface =1. When both α and γ are at their minimum values (i.e., α=5, γ=0.2), then σ=103.5; when both α and γ are at their maximum values (i.e., α=15, γ=1), then σ=113.6. In this case, σ is between 103.5 and 113.6.
[0086] In another example, σ(Cu) = 98.7, D = 0.97, F = 0.92, δ surface =0. When α is at its minimum value (i.e., α=5), then σ=103.4; when α is at its maximum value (i.e., α=15), then σ=112.7. In this case, σ is between 103.5 and 112.7.
[0087] In some embodiments of this application, the tensile strength of the graphene-copper composite wire is ≥230 MPa.
[0088] Graphene itself possesses extremely high mechanical strength. Introducing graphene into the copper matrix, as a reinforcement, increases the tensile strength of the graphene-copper composite wire core 1, thereby enhancing the tensile strength of the graphene-copper composite wire. This increased tensile strength, when used as a winding in motor windings, improves the structural rigidity of the windings, enhancing their radial strength and resistance to instability.
[0089] In some embodiments of this application, the graphene-copper composite wire is a flat wire with a width of 4mm to 20mm and a thickness of 2mm to 10mm. As an example, the width of the flat wire is 4mm, 6mm, 8mm, 10mm, 12mm, 14mm, 16mm, 18mm or 20mm; and the thickness is 2mm, 4mm, 6mm, 8mm or 10mm.
[0090] This application also provides a method for preparing a graphene-copper composite wire, which is used to prepare the aforementioned graphene-copper composite wire. The method for preparing the graphene-copper composite wire includes: Graphene was grown on the surface of copper material by chemical vapor deposition to obtain a graphene-copper composite material. The graphene-copper composite material was subjected to hot pressing and sintering to form the graphene-copper composite wire core 1, thus obtaining the graphene-copper composite wire.
[0091] The method for preparing graphene-copper composite wire provided in this application grows graphene on the surface of raw material (copper material) through chemical vapor deposition (CVD) and achieves material densification through hot pressing sintering. This results in a uniform distribution of highly conductive graphene network inside the graphene-copper composite wire core 1, significantly improving the conductivity of the graphene-copper composite wire. This provides a new solution for the design of high-performance motor windings and optimizes the heat dissipation capacity during motor winding operation, reducing the heat generation of the motor at high speeds, increasing the motor's maximum speed, and significantly improving the motor's performance.
[0092] Unlike traditional motor wire casting, extrusion, and drawing processes, the embodiments of this application directly process the raw materials into shape, avoiding the damage to the graphene network caused by grain breakage and recrystallization during deformation processing, thus greatly bringing out the excellent properties of graphene in motor winding products.
[0093] In some embodiments of this application, the chemical vapor deposition process includes a first heating stage, a reduction stage, a first growth stage, and a first cooling stage; The first heating stage meets the following conditions: the heating temperature is 900℃~1050℃, the heating rate is 10℃ / min~20℃ / min, the atmosphere includes argon, and the flow rate of argon is 10sccm~500sccm. The reduction stage meets the following conditions: the reduction temperature is 900℃~1050℃, the time is 1h~5h, the atmosphere includes hydrogen, and the hydrogen flow rate is 100sccm~3000sccm. The first growth stage meets the following conditions: the growth temperature is 900℃~1050℃, the atmosphere includes argon, hydrogen and methane, and the flow rate of argon is 100sccm~500sccm, the flow rate of hydrogen is 10sccm~500sccm, the flow rate of methane is 1sccm~30sccm, and the time is 20min~60min. The first cooling stage meets the following conditions: the cooling rate is 10℃ / min to 20℃ / min, the atmosphere includes argon, and the argon flow rate is 10 sccm to 500 sccm.
[0094] Copper material is placed in a CVD device, and after heating, reduction, growth and cooling stages, a high-quality thin layer of graphene is uniformly grown on the surface of the raw material to obtain a graphene copper composite material.
[0095] In the graphene-copper composite material prepared by the above-mentioned chemical vapor deposition method, graphene (specifically, second graphene) is attached to the surface of the copper material; the graphene coverage rate on the copper surface is ≥98%, the proportion of single and double-layer graphene with two or fewer layers is ≥95%, and the proportion of single-layer graphene is ≥80%. By increasing the proportion of graphene with fewer layers in the graphene-copper composite material, the content of graphene with fewer layers in the graphene-copper composite wire core 1 obtained by subsequent hot pressing and sintering can be further increased, thereby improving the electrical and thermal conductivity of the graphene-copper composite wire.
[0096] As an example, the heating temperature in the first heating stage is 900℃, 950℃, 1000℃ or 1050℃, the heating rate is 10℃ / min, 12℃ / min, 14℃ / min, 16℃ / min, 18℃ / min or 20℃ / min, and the argon flow rate is 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm or 500 sccm.
[0097] As an example, the reduction temperature during the reduction stage is 900℃, 950℃, 1000℃, or 1050℃, the time is 1h, 2h, 3h, 4h, or 5h, and the hydrogen flow rate is 100sccm, 500sccm, 1000sccm, 1500sccm, 2000sccm, 2500sccm, or 3000sccm.
[0098] As an example, the growth temperature of the first growth stage is 900℃, 950℃, 1000℃ or 1050℃, the argon flow rate is 100sccm, 200sccm, 300sccm, 400sccm or 500sccm, the hydrogen flow rate is 10sccm, 100sccm, 200sccm, 300sccm, 400sccm or 500sccm, the methane flow rate is 1sccm, 5sccm, 10sccm, 15sccm, 20sccm or 30sccm, and the time is 20min, 30min, 40min, 50min or 60min.
[0099] As an example, the cooling rate of the first cooling stage is 10℃ / min, 12℃ / min, 14℃ / min, 16℃ / min, 18℃ / min or 20℃ / min, and the argon flow rate is 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm or 500 sccm.
[0100] In some embodiments of this application, the sintering temperature of the hot pressing sintering process is 700℃~900℃, the sintering pressure is 20MPa~60MPa, and the holding time is 20min~60min.
[0101] By controlling the sintering temperature and holding time of the hot pressing sintering process within the above range, the carbon loss rate of the graphene copper composite core 1 formed after hot pressing sintering of graphene copper composite material can be ≤5%.
[0102] As an example, the sintering temperature is 700℃, 750℃, 800℃, 850℃ or 900℃, the sintering pressure is 20Mpa, 30Mpa, 40Mpa, 50Mpa or 60Mpa, and the holding time is 20min, 30min, 40min, 50min or 60min.
[0103] In some embodiments of this application, the graphene copper composite material is placed into a hot pressing mold for hot pressing sintering. The size of the hot pressing mold is designed according to the requirements, and the graphene copper composite wire core 1 that meets the size requirements of the winding wire is directly prepared.
[0104] The graphene-copper composite material is placed in a hot press mold according to the winding core specifications and hot press sintering is carried out in one step to prepare the core of the motor winding wire. After the core is prepared, there is no need to draw or anneal, thus avoiding the damage to the graphene network caused by drawing stress or annealing recrystallization.
[0105] By controlling the temperature and pressure of the hot pressing sintering process, the dimensional accuracy of the obtained graphene copper composite wire core 1 can be guaranteed, and the wire can be directly formed and applied to windings.
[0106] In some embodiments of this application, the hot pressing sintering process includes at least one of static hot pressing sintering with a mold, continuous hot extrusion molding of powder, and spark plasma sintering (SPS).
[0107] In some embodiments of this application, the preparation method of graphene copper composite wire further includes: coating the surface of graphene copper composite wire core 1 with a graphene layer 2.
[0108] By coating the surface of the graphene-copper composite core 1 with a layer of graphene structure, a synergistic effect of high conductivity and high heat dissipation is achieved.
[0109] In some embodiments of this application, a graphene layer 2 is coated on the surface of the graphene-copper composite core 1 using plasma-enhanced chemical vapor deposition.
[0110] Plasma-enhanced chemical vapor deposition (PECVD) technology was used to re-grow and coat graphene on the surface of graphene-copper composite core 1, thereby obtaining the final graphene-copper composite wire. This process was carried out at relatively low temperatures (≤600℃), utilizing plasma excitation to achieve graphene growth and coating at lower temperatures. This avoided the impact of high-temperature grain growth on the internal structure of graphene-copper composite core 1, while simultaneously achieving graphene growth on the wire surface, further improving the wire's heat dissipation and conductivity.
[0111] In some embodiments of this application, the plasma-enhanced chemical vapor deposition process includes a second heating stage, a cleaning stage, a second growth stage, and a second cooling stage. The second heating stage meets the following conditions: the heating temperature is 300℃~600℃, the heating rate is 10℃ / min~20℃ / min, the atmosphere includes argon, and the argon flow rate is 10sccm~500sccm. The cleaning stage meets the following conditions: temperature 300℃~600℃, radio frequency power 50W~500W, pressure 100Pa~5000Pa, time 10min~60min, atmosphere includes argon, and the flow rate of argon is 10sccm~500sccm. The second growth stage meets the following conditions: growth temperature is 300℃~600℃, radio frequency power is 50W~500W, pressure is 100Pa~5000Pa, time is 10min~60min, atmosphere includes argon, hydrogen and methane, and the flow rate of argon is 10sccm~500sccm, the flow rate of hydrogen is 10sccm~500sccm, and the flow rate of methane is 1sccm~20sccm. The second cooling stage meets the following conditions: the cooling rate is 10℃ / min to 20℃ / min, the atmosphere includes argon, and the argon flow rate is 10 sccm to 500 sccm.
[0112] It can be seen that, compared with the above-mentioned method of growing graphene on the surface of copper material by chemical vapor deposition, the method of coating graphene layer 2 on the surface of graphene copper composite core 1 by plasma-enhanced chemical vapor deposition has a lower temperature in both the heating and growth stages than the thickness temperature. This combination can form a synergistic effect between highly conductive graphene copper composite core 1 and highly heat-dissipating graphene layer 2.
[0113] As an example, the heating temperature in the second heating stage is 300℃, 350℃, 400℃, 450℃, 500℃, 550℃ or 600℃, the heating rate is 10℃ / min, 12℃ / min, 14℃ / min, 16℃ / min, 18℃ / min or 20℃ / min, and the argon flow rate is 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm or 500 sccm.
[0114] As an example, the temperature of the cleaning stage is 300℃, 350℃, 400℃, 450℃, 500℃, 550℃ or 600℃, the radio frequency power is 50W, 100W, 200W, 300W, 400W or 500W, the pressure is 100Pa, 500Pa, 1000Pa, 2000Pa, 3000Pa, 4000Pa or 5000Pa, the time is 10min, 20min, 30min, 40min, 50min or 60min, and the hydrogen flow rate is 10sccm, 100sccm, 200sccm, 300sccm, 400sccm or 500sccm.
[0115] As an example, the growth temperature of the second growth stage is 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, or 600℃; the radio frequency power is 50W, 100W, 200W, 300W, 400W, or 500W; the pressure is 100Pa, 500Pa, 1000Pa, 2000Pa, 3000Pa, 4000Pa, or 5000Pa; and the time is 10min, 20min, 30min, or 40min. The flow rates are 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm, or 500 sccm for 50 min, 50 min, or 60 min for argon, 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm, or 500 sccm for hydrogen, and 1 sccm, 5 sccm, 10 sccm, 15 sccm, or 20 sccm for methane.
[0116] As an example, the cooling rate of the second cooling stage is 10℃ / min, 12℃ / min, 14℃ / min, 16℃ / min, 18℃ / min or 20℃ / min, and the argon flow rate is 10 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm or 500 sccm.
[0117] In some embodiments of this application, a graphene layer 2 is coated on the surface of the graphene-copper composite wire core 1, including: The graphene-copper composite wire core 1 is immersed in graphene slurry and dried to obtain graphene layer 2.
[0118] In some embodiments of this application, the preparation method of the graphene-copper composite wire further includes polishing the surface of the graphene-copper composite wire core 1 before coating with the graphene layer 2. The graphene-copper composite wire core 1 obtained by hot pressing and sintering is polished to remove surface impurities, thereby improving the bonding effect between the graphene layer 2 and the graphene-copper composite wire core 1. As an example, the polishing treatment includes at least one of mechanical polishing, magnetic polishing, acid pickling, and electrolytic polishing.
[0119] In some embodiments of this application, the preparation method of graphene copper composite wire further includes: coating the surface of graphene layer 2 with an insulating layer 3.
[0120] In some embodiments of this application, an insulating layer 3 is coated onto the surface of the graphene layer 2 using a mold coating method. The mold coating has 10 to 20 coating passes, the drying temperature is 350°C to 450°C, and the drying time for each pass is 5 to 20 seconds.
[0121] After coating the surface of the graphene copper composite wire core 1 with a graphene layer 2, an insulating varnish is uniformly applied to the surface of the wire using a coating mold. The wire is then dried in an oven, and this process is repeated several times until the varnish film thickness meets the requirements, thus obtaining a high-performance graphene copper composite wire that can be used for motor windings.
[0122] This application also provides a winding comprising the above-mentioned graphene-copper composite wire or the graphene-copper composite wire prepared by the above-mentioned method.
[0123] This application also provides an electric motor, including the aforementioned windings.
[0124] The following description is based on specific embodiments.
[0125] Example 1 S1. Using high-purity copper powder with a purity ≥ 99.999% as raw material, the high-purity copper powder is placed in a CVD furnace for chemical vapor deposition to grow graphene. CVD process parameters: Heating stage: Heating temperature 1000℃, heating rate 10℃ / min, 200sccm argon atmosphere protection; Reduction stage: reduction temperature is 1000℃, time is 2h, atmosphere is hydrogen, flow rate is 1000sccm; Growth stage: The growth temperature is 1000℃, the atmosphere is argon, hydrogen and methane, the argon flow rate is 200 sccm, the hydrogen flow rate is 40 sccm, the methane flow rate is 20 sccm, and the time is 30 min. Cooling stage: The cooling rate is 18℃ / min, the atmosphere is argon, the flow rate is 200sccm, and a graphene layer is uniformly grown on the surface of copper powder to obtain graphene copper composite powder.
[0126] The graphene-copper composite powder has a graphene coating rate of 99%, with a single-layer and double-layer rate of 99% and a single-layer rate of 95%.
[0127] S2. The graphene-copper composite powder obtained in step S1 is placed into a 4.5mm×6mm hot-pressing sintering mold for hot-pressing sintering. The sintering temperature is set to 700℃, the sintering pressure to 50MPa, and the holding time to 60min. This step yields a graphene-copper composite wire core. The surface of the graphene-copper composite wire core prepared by hot-pressing sintering is then magnetically polished to remove some impurities and oxides from the surface.
[0128] Among them, the graphene surface distribution rate in the graphene copper composite wire core is 97%, of which single and double layer graphene accounts for 91%, that is, the single and double layer graphene surface distribution rate in this region is 88.27%, of which single layer graphene accounts for 80%, that is, the single layer graphene surface distribution rate in this region is 77.60%.
[0129] S3. Graphene is grown on the surface of the polished graphene-copper composite wire core using PECVD. The PECVD process parameters are as follows: Heating stage: Temperature is 500℃, heating rate is 10℃ / min, atmosphere is argon, flow rate is 200sccm; Cleaning stage: temperature 500℃, radio frequency power 300W, pressure 400Pa, time 30min, atmosphere argon, flow rate 50sccm; Growth stage: temperature 500℃, radio frequency power 300W, pressure 400Pa, time 20min, atmosphere argon, hydrogen and methane, argon flow rate 100sccm, hydrogen flow rate 40sccm, methane flow rate 10sccm. Cooling stage: The cooling rate is 18℃ / min, the atmosphere is argon, the flow rate is 200sccm, and graphene is uniformly grown on the surface of the graphene copper composite wire core to obtain the graphene copper composite wire.
[0130] The graphene copper composite wire has a graphene surface distribution rate of 99%, of which single and double layer graphene accounts for 97%, and single layer graphene accounts for 86%.
[0131] S4. The wire prepared in step S3 is coated with insulating varnish. The insulating varnish is polyester varnish. The coating method is mold coating. There are 10 coating passes. The oven temperature is 350℃. After curing, the finished product is obtained.
[0132] Example 2 The difference between Example 2 and Example 1 is as follows: In order to obtain a higher coating rate and a thicker powder layer in the powder stage, the growth temperature in S1 was increased to 1050℃, the hydrogen flow rate was increased to 100 sccm, and the growth time was reduced to 20 min. The graphene coating rate of the graphene-copper composite powder obtained in S1 was 99%, of which the single-layer / double-layer ratio was 62% and the single-layer ratio was 31%. The graphene surface distribution rate in the graphene-copper composite wire core obtained in S2 was 95%, of which the single-layer / double-layer graphene accounted for 55%, that is, the single-layer / double-layer graphene surface distribution rate in this region was 52.25%, of which the single-layer graphene accounted for 27%, that is, the single-layer graphene surface distribution rate in this region was 25.65%.
[0133] Example 3 The difference between Example 3 and Example 1 is that in S1, the growth temperature during the growth stage was reduced to 950℃, the methane flow rate was reduced to 15 sccm, and the growth time was increased to 40 min. The graphene coating rate of the graphene-copper composite powder obtained in S1 was 76%, of which the single-layer / double-layer ratio was 93% and the single-layer ratio was 91%. The subsequent molding process was the same as in Example 1. In S2, the graphene surface distribution rate in the graphene-copper composite wire core was 69%, of which the proportion of single-layer / double-layer graphene was 87%, that is, the single-layer / double-layer graphene surface distribution rate in this region was 60.03%, of which the proportion of single-layer graphene was 85%, that is, the single-layer graphene surface distribution rate in this region was 58.65%.
[0134] Example 4 The difference between Example 4 and Example 1 is that in S1, the growth temperature during the growth stage was reduced to 950℃, the hydrogen flow rate was reduced to 20 sccm, and the growth time was reduced to 20 min. The graphene coating rate of the graphene-copper composite powder obtained in S1 was 84%, of which the single-layer / double-layer ratio was 54%, and the single-layer ratio was 42%. The subsequent molding process was the same as in Example 1. In S2, the graphene surface distribution rate in the graphene-copper composite wire core was 77%, of which the proportion of single-layer / double-layer graphene was 48%, that is, the single-layer / double-layer graphene surface distribution rate in this region was 32.68%, of which the proportion of single-layer graphene was 33%, that is, the single-layer graphene surface distribution rate in this region was 25.08%.
[0135] Example 5 The difference between Example 5 and Example 1 is that no graphene layer was grown on the surface of the wire by PECVD, that is, step S3 was omitted.
[0136] Example 6 The difference between Example 6 and Example 1 is that in S1, the methane flow rate during the growth stage is increased to 30 sccm, and the growth time is increased to 50 min. The graphene-copper composite powder obtained in S1 has a surface graphene coating rate of 93%, of which the single-layer / double-layer ratio is 45%, and the single-layer ratio is 25%. The subsequent molding process is the same as in Example 1. In S2, the graphene surface distribution rate in the graphene-copper composite wire core is 81%, of which the proportion of single-layer / double-layer graphene is 40%, that is, the single-layer / double-layer graphene surface distribution rate in this region is 32.4%, of which the proportion of single-layer graphene is 18%, that is, the single-layer graphene surface distribution rate in this region is 14.58%.
[0137] Comparative Example 1 Purchase high-quality, high-purity oxygen-free copper wire (purity ≥ 99.999%) of the same specifications available on the market, and directly coat it with an insulating varnish film. The coating process is the same as step S4 in Example 1.
[0138] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in S1, the methane flow rate during the growth stage was significantly reduced to 5 sccm, and the growth time was shortened to 10 min, resulting in insufficient graphene growth. The graphene-copper composite powder obtained in S1 had a surface graphene coating rate of only 65%, but due to the slow growth, its quality was high, with a single-layer / double-layer ratio of 90% and a single-layer ratio of 80%. The subsequent molding process was the same as in Example 1. In the graphene-copper composite wire core obtained in S2, due to insufficient coating, the graphene surface distribution rate was only 60%, with single-layer / double-layer graphene accounting for 85%, meaning the single-layer / double-layer graphene surface distribution rate in this region was 51.00%, and single-layer graphene accounting for 75%, meaning the single-layer graphene surface distribution rate in this region was 45.00%.
[0139] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that graphene was not grown in situ on the copper substrate using chemical vapor deposition (CVD), but instead a traditional mechanical powder mixing process was employed. Specifically, commercially available multilayer graphene powder (with a single-layer / double-layer ratio of approximately 70%) and high-purity copper powder with a purity ≥99.999% were fed into a high-energy ball mill and ball-milled for 2 hours under argon protection to obtain a mixed powder. The subsequent molding process was the same as in Example 1. The graphene-copper composite wire core obtained in S2 exhibited significant graphene agglomeration, resulting in a graphene surface distribution rate of only 55%. Furthermore, the graphene structure was somewhat damaged during ball milling. The proportion of single-layer / double-layer graphene was 38%, meaning the single-layer / double-layer graphene surface distribution rate in this region was 20.90%, with single-layer graphene accounting for 20%, meaning the single-layer graphene surface distribution rate in this region was 11.00%.
[0140] Performance testing: 1. Graphene surface distribution test: The surface distribution rate of graphene in graphene-copper composite wire cores was tested using a statistical characterization method based on microscopic Raman lattice scanning, which characterized the high-density uniform spatial distribution of graphene in copper substrates.
[0141] Characterization Method: The longitudinal axis of the graphene-copper composite wire core was mechanically cut to obtain the test section. After polishing the test section to remove surface impurities, the sample was tested using a micro-confocal Raman spectrometer. The core test parameters were limited as follows: laser wavelength of 532 nm; spot focusing diameter < 1 μm; and at least M (M ≥ 3) spatially non-overlapping designated unit areas were randomly selected on the test section using a spatial dot matrix scanning strategy. The macroscopic size of the designated unit area was L × W (limited to a 100 μm × 100 μm region in this embodiment). A high-precision two-dimensional electric displacement stage was used to plan the scanning path in a grid-like dot matrix form within the 100 μm × 100 μm designated unit area. The horizontal (X-axis) step size and the vertical (Y-axis) step size were both set to 10 μm. A total of 10 × 10 = 100 independent micro-observation points were uniformly collected within a single designated unit area. Raman spectra were collected from each micro-observation site, and the region located at 1580±15 cm⁻¹ was extracted from the Raman spectra. -1 The intensity of the G peak at (I) G ) and located at 2700±30cm -1 2D peak intensity (I) at 2D To determine whether a test point has a "valid graphene characteristic signal", the following criteria must be met simultaneously: (1) Peak presence: in I G and I 2D Within the region, the intensity of its signal peaks is more than 3 times greater than the standard deviation of the baseline background noise (i.e., signal-to-noise ratio > 3); (2) Structural characteristics: the I G Peak and I 2D The peak intensity ratio satisfies: I 2D / I G >0.2, where I 2D / I G Sites with a value greater than 2 are identified as single-layer graphene sites, where 2 > 1. 2D / I G Sites with a value greater than 1 are identified as bilayer graphene sites, where 1 > 1. 2D / I G Points with a value >0.2 are identified as multilayer graphene points. If a test point simultaneously meets the above criteria (1) and (2), then the point is recorded as a "positive signal point"; otherwise, if a characteristic peak is missing or only the D peak of amorphous carbon (1350 cm⁻¹) is present, the point is considered a positive signal point. -1If the positive signal point is located in the vicinity of the micro-region, it is denoted as a "zero signal point". The percentage of all positive signal points observed in the current micro-region by the graphene-copper composite core is defined as the surface distribution rate of graphene in that region. The test results are shown in Table 1.
[0142] In this embodiment, the graphene-copper composite wire core exhibits a graphene surface distribution rate ≥69% within any defined unit area of its cross-section, with single-layer and double-layer graphene accounting for ≥43%, meaning a single-layer and double-layer graphene surface distribution rate ≥32% within this region. Furthermore, single-layer graphene accounts for ≥27%, meaning a single-layer graphene surface distribution rate ≥25% within this region. This indicates that the graphene-copper composite wire core prepared by the method described in this application can effectively retain the high-quality graphene properties of the raw material powder.
[0143] 2. Carbon content test: Carbon content is a crucial indicator for evaluating the graphene content in wire. Since graphene is entirely composed of carbon, changes in carbon content during processing directly reflect the changes in graphene during its fabrication. Comparing the carbon content in the hot-pressed sintered wire with that in the graphene-copper composite powder grown by CVD (Chemical Vapor Deposition) indicates the retention of graphene under the given processing conditions. A significant change in carbon content signifies that the structural integrity of the graphene in the wire has been compromised during processing. The specific testing method involves precisely measuring the carbon content of the graphene-copper composite wire core after processing and comparing the result with the carbon content of the original graphene-copper composite powder grown by chemical vapor deposition. The ratio between the two is defined as the carbon loss rate.
[0144] Characterization method: The determination was carried out according to the national standard GB / T 20123-2006 "High-frequency combustion infrared absorption method", and quantitative detection was performed using a high-frequency infrared carbon-sulfur analyzer. The test results are shown in Table 1.
[0145] In the embodiments of this application, the carbon loss rate of the graphene copper composite wire core is ≤5%.
[0146] 3. Conductivity test: Characterization Method: A precision four-column DC bridge method (DC double-arm bridge method) was used for measurement, with a 1200mm long graphene copper composite wire selected as the standard test sample. The test was conducted in a temperature-controlled shielded room, with the ambient temperature strictly controlled at 20±2℃ and humidity not exceeding 60%. The four-column bridge adopted a four-terminal measurement structure: the two outer terminals (C1, C2) were current terminals, through which a constant DC current I was applied; the two inner terminals (P1, P2) were potential terminals used to measure the voltage drop V. This method is based on the potential difference balance principle of the double-arm bridge, which can completely eliminate the influence of the test lead resistance and contact resistance on the measurement results, and is suitable for precision measurement of low-resistance metal wires. The measurement current I was set to 1A~5A. The resistance R = V / I was calculated based on the measured voltage drop V, and then the formula ρ = R... The volume resistivity of the sample was calculated using the S / L ratio, where S is the cross-sectional area of the conductor (obtained by observing the cross-section using a metallographic microscope and extracting the pixel area using software), and L is the distance between the two inner potential terminals (L is taken as 1000 mm according to the national standard GB / T 351-2019). The volume resistivity was then converted to %IACS percentage. The test results are shown in Table 1.
[0147] The graphene-copper composite wire provided in this application achieves excellent conductivity by constructing a high-density, continuous graphene conductive network within a copper matrix. The conductivity values described in this application are characterized as percentages (%IACS) based on the International Standard for Annealed Copper. At room temperature (20±2℃), the conductivity of the graphene-copper composite wire in this application ranges from 105%IACS to 111%IACS. This high conductivity characteristic is attributed to the synergistic electron transport channels formed by graphene within the copper matrix, effectively reducing the scattering resistance of electrons at grain boundaries.
[0148] 4. Thermal conductivity test: Characterization method: Thermal conductivity was tested using an LAF thermal conductivity meter. The graphene-copper composite wire sample was cut, polished, and placed in a specific test fixture to directly test the thermal conductivity of the material. The test results are shown in Table 1.
[0149] By further coating the surface of the graphene copper composite core with a graphene layer, the heat dissipation performance of the material is significantly improved. In addition, the continuous graphene network inside the graphene copper composite core increases the conductivity of the product, further reducing the heat generation phenomenon of the product under actual working conditions. At the same time, the thermal conductivity can also further confirm the integrity of the graphene network in the graphene copper composite core. The more complete the graphene network, the better the thermal conductivity of the core.
[0150] Under normal temperature (25±1℃) conditions, the thermal conductivity of the graphene copper composite wire in the embodiments of this application is ≥420 W / (m·K) along the axial direction (length direction), and can be selected as 420W / (m·K)~500W / (m·K).
[0151] Table 1
[0152] 5. Graphene micro-size measurement: Since the graphene thickness in the graphene-copper composite core in this application embodiment is mainly single or double layer (1-2 layers), after the conventional silicon wafer transfer method completely etches the copper substrate, the surface tension of the etching solution will further damage the graphene, making it impossible to observe the depth of the graphene well. Therefore, this application adopts the surface micro-etching method, which etches the surface to a micrometer-level depth using an etching solution, and uses the copper substrate as a base to support the single or double layer graphene. The graphene is observed using a scanning electron microscope (SEM), and the graphene sheet size is statistically analyzed using image analysis software to characterize the distribution of graphene in the substrate.
[0153] Characterization method: The graphene-copper composite core sample, after hot pressing and polishing, was mechanically cut along the longitudinal axis to expose a clean longitudinal section. The section was then immersed in a prepared micro-etching solution (which can be a 1:100 volume ratio dilute nitric acid aqueous solution or an equivalent ferric chloride-hydrochloric acid-ethanol solution) for slight surface etching. The etching time was strictly controlled between 3s and 8s, allowing the copper substrate on the surface to be locally peeled off to a depth of 1μm to 3μm, while the in-situ attached graphene sheets remained on the surface of the copper substrate "base". Figure 3 The image shown is a SEM image of the graphene sheets after micro-etching on the surface of the graphene-copper composite wire core in Example 1. After etching, the samples were quickly cleaned with deionized water and anhydrous ethanol and then dried. Subsequently, the samples were placed under a field emission scanning electron microscope (FE-SEM) at an accelerating voltage of 3kV~5kV and a working distance of 5mm~10mm for morphological observation, and at least five representative field-of-view graphene images were randomly captured. Color thresholding and grain contour extraction were performed using image analysis software, and the average lateral equivalent size of the graphene sheets was statistically calculated. The test results are shown in Table 2.
[0154] Table 2
[0155] Results analysis: As can be seen from Table 1, the graphene-copper composite wire prepared in Example 1 has a conductivity of up to 111.08% IACS, which is 12.38% higher than that of pure copper (Comparative Example 1) with 98.7% IACS. The thermal conductivity of the material is also increased to 492 W / (m·K), which is about 23.3% higher. However, it still has a very high gain compared to traditional pure copper.
[0156] A comparison between Example 1 and Example 2 shows that, while maintaining similar surface distribution rates, a decrease in graphene quality (single / double layer ratio) will also affect product performance. However, compared to the impact of surface distribution rate, the influence of graphene quality on the product is relatively small.
[0157] A comparison between Example 1 and Example 3 shows that a slight decrease in the graphene surface distribution rate inside the graphene copper composite wire core will have a direct impact on the electrical and thermal conductivity of the final graphene copper composite wire. When the graphene quality (single and double layer ratio) is similar, a decrease in the graphene surface distribution rate from 97% to 69% will result in a decrease in the electrical and thermal conductivity of the final product to varying degrees.
[0158] A comparison of Examples 1 and 4 shows that when the graphene surface distribution rate and the single / double layer ratio within the graphene-copper composite wire core are both reduced, the conductivity enhancement effect brought by the graphene network is significantly reduced. Furthermore, the thermal conductivity of the product also decreases substantially.
[0159] Comparing the test results of Example 1 and Example 5, it can be seen that the introduction of the graphene layer on the surface of the graphene copper composite wire core not only slightly assists the conductivity of the graphene copper composite wire (suppressing the local impedance growth caused by the skin effect), but also significantly optimizes the overall heat dissipation performance (axial and radial thermal conductivity) of the graphene copper composite wire.
[0160] A comparison between Example 1 and Example 6 shows that although the graphene surface distribution rate inside the graphene copper composite wire core is relatively high, the quality of the graphene is not high, resulting in low conductivity and thermal conductivity of the final product.
[0161] A comparison of Example 1 and Comparative Example 1 shows that introducing graphene into the interior and surface of the copper substrate can significantly improve the electrical conductivity and thermal conductivity of the product.
[0162] A comparison between Example 1 and Comparative Example 2 shows that although the graphene is of high quality, the graphene surface distribution rate inside the graphene-copper composite wire core is low, and the overall carbon content of the graphene-copper composite wire is also low. The conductivity enhancement effect brought by the graphene network is not obvious, and the conductivity and thermal conductivity of the finished product are not high.
[0163] Through the comparison between Example 1 and Comparative Example 3, it can be seen that when the quality of graphene is low and the areal distribution rate of graphene inside the graphene-copper composite wire core is low, the electrical conductivity and thermal conductivity of the finished product are low.
[0164] As can be seen from the analysis of the test results in Table 1, the high-performance graphene-copper composite wire prepared in the examples of the present application exhibits a significant enhancement effect in electrical conductivity. Specifically, the microscopic spatial structure parameters of graphene in the examples of the present application and the value σ of the room-temperature electrical conductivity of the graphene-copper composite wire satisfy the following equation:
[0165] In the equation, σ is the value of the final electrical conductivity of the graphene-copper composite wire; σ(Cu) is the value of the initial electrical conductivity of the pure copper matrix. The graphene conductive network mainly exerts its enhancement effect in the composite material, so σ(Cu) ranges from 98 to 103 according to the difference in the type of the selected copper matrix. According to the test result of Comparative Example 1, a fixed value (98.7) is taken for σ(Cu) in the practice of the present application; D is the areal distribution rate of graphene in the cross-section of the graphene-copper composite wire core measured by micro-Raman lattice scanning (expressed as a decimal, 0<D<1); F is the single-layer and double-layer rate of graphene in the graphene-copper composite wire core (expressed as a decimal, 0<F<1); δ surface is the characteristic position state value of the surface graphene. When a graphene layer is grown on the surface of the graphene-copper composite wire through the PECVD process, δ surface =1, and when no graphene layer is grown, δ surface = 0; α is the internal network synergistic conductivity enhancement coefficient, which ranges from 5 to 15, and optionally, α is 12.5; γ is the surface graphene synergistic effect factor, which ranges from 0.2 to 1.0, and optionally, γ is 0.5.
[0166] Further, in order to prove the accuracy and universality of the above equation, the microstructure characteristic parameters of each example and the key comparative examples of the present application are substituted into the equation for calculation. The comparison between the theoretical fitting results and the actual experimental measurement values and the error analysis are shown in Table 3: Table 3
[0167] It can be seen from the data verification results in Table 3 that the absolute value of the relative error between the theoretical calculated value of the electrical conductivity of each group by the above equation and the actual test value is less than 0.5%IACS. It shows that the equation has good scientificity and high accuracy, and further reveals the deep physical essence of the response of each microscopic morphology parameter to the macroscopic electric field.
[0168] As can be seen from Table 2, the equivalent size of the graphene sheets in Example 1 is mainly concentrated in the range of 5μm to 10μm (accounting for 53%). Due to the relatively high single-to-double layer ratio, the continuous single-layer graphene may be damaged due to the surface tension of the etching solution, resulting in a significantly higher number of graphene sheets. In Example 2, the single-to-double layer ratio is relatively low, and most of the sheets are thick-layer structures. The thick-layer graphene framework is more easily preserved, so the size of the graphene sheets is larger. In Example 3, the number of graphene sheets also decreases significantly due to the reduced graphene surface distribution rate.
[0169] The foregoing has provided a detailed description of a graphene-copper composite wire, its preparation method, and its winding provided in the embodiments of this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A graphene-copper composite wire, characterized in that, include: A graphene-copper composite wire core includes a copper matrix and a first graphene distributed inside the copper matrix, wherein the surface distribution rate of the first graphene in the graphene-copper composite wire core is ≥69%.
2. The graphene-copper composite wire according to claim 1, characterized in that, The surface distribution rate of the first graphene in the single or double layer of the graphene-copper composite wire core is ≥32%; and / or, The surface distribution of the first graphene layer in the graphene-copper composite wire core is ≥25%.
3. The graphene-copper composite wire according to claim 1, characterized in that, The single / double layer ratio of the first graphene in the graphene-copper composite wire core is ≥48%; and / or, The monolayer ratio of the first graphene in the graphene-copper composite wire core is ≥27%.
4. The graphene-copper composite wire according to claim 1, characterized in that, The graphene-copper composite core is obtained by hot pressing and sintering of graphene-copper composite material, which includes copper material and a second graphene material attached to the surface of the copper material.
5. The graphene-copper composite wire according to claim 4, characterized in that, In the graphene-copper composite material, the second graphene has a coating rate of ≥76% on the copper surface; and / or, The single-layer / double-layer ratio of the second graphene in the graphene-copper composite material is ≥54%; and / or, The monolayer ratio of the second graphene in the graphene-copper composite material is ≥31%; and / or, Compared to the graphene-copper composite material, the carbon loss rate of the graphene-copper composite wire core is ≤5%.
6. The graphene-copper composite wire according to claim 1, characterized in that, The graphene copper composite wire also includes a graphene layer, which wraps around the surface of the graphene copper composite wire core.
7. The graphene-copper composite wire according to claim 6, characterized in that, The carbon content in the graphene-copper composite wire is 50ppm to 180ppm.
8. The graphene-copper composite wire according to claim 6, characterized in that, The graphene-copper composite wire also includes an insulating layer that wraps around the surface of the graphene layer.
9. The graphene-copper composite wire according to any one of claims 1 to 8, characterized in that, The conductivity of the graphene-copper composite wire is 105% IACS ~ 115% IACS; and / or, The thermal conductivity of the graphene-copper composite wire is ≥420W / (m·K).
10. The graphene-copper composite wire according to any one of claims 1 to 8, characterized in that, The room temperature conductivity σ of the graphene-copper composite wire satisfies the following relationship: ; In the formula, σ(Cu) is the value of the initial electrical conductivity of the pure copper matrix, and the units of the normal-temperature electrical conductivity and the initial electrical conductivity are %IACS; D is the areal distribution ratio of the first graphene in the graphene-copper composite wire core, 0<D<1; F is the single-to-bilayer ratio of the first graphene in the graphene-copper composite wire core, 0<F<1; δ surface is the characteristic position state value of the surface graphene of the graphene-copper composite wire, and when the graphene-copper composite wire comprises a graphene layer, δ surface =1, and when the graphene-copper composite wire does not comprise a graphene layer, δ surface = 0; α is the internal network synergistic electrical conductivity enhancement coefficient of the graphene-copper composite wire, with a value range of 5 to 15; γ is the surface graphene synergistic effect factor of the graphene-copper composite wire, with a value range of 0.2 to 1.
0.
11. The method for preparing the graphene-copper composite wire according to any one of claims 1 to 10, characterized in that, include: Graphene was grown on the surface of copper material by chemical vapor deposition to obtain a graphene-copper composite material. The graphene-copper composite material is subjected to hot pressing and sintering to form a graphene-copper composite wire core, thereby obtaining a graphene-copper composite wire.
12. The method for preparing the graphene-copper composite wire according to claim 11, characterized in that, The chemical vapor deposition process includes a first heating stage, a reduction stage, a first growth stage, and a first cooling stage; the heating temperature of the first heating stage is 900℃~1050℃; the reduction temperature of the first reduction stage is 900℃~1050℃; the growth temperature of the first growth stage is 900℃~1050℃; the cooling rate of the first cooling stage is 10℃ / min~20℃ / min; and / or, The hot pressing sintering treatment has a sintering temperature of 700℃~900℃, a sintering pressure of 20Mpa~60Mpa, and a holding time of 20min~60min.
13. The method for preparing the graphene-copper composite wire according to claim 11 or 12, characterized in that, The preparation method of the graphene copper composite wire further includes: coating the surface of the graphene copper composite wire core with a graphene layer.
14. The method for preparing the graphene-copper composite wire according to claim 13, characterized in that, The graphene layer is coated onto the surface of the graphene-copper composite wire core using plasma-enhanced chemical vapor deposition (PECVD). The PECVD process includes a second heating stage, a cleaning stage, a second growth stage, and a second cooling stage. The heating temperature in the second heating stage is 300℃~600℃; the cleaning temperature is 300℃~600℃; the growth temperature in the second growth stage is 300℃~600℃; and the cooling rate in the second cooling stage is 10℃ / min~20℃ / min; and / or, Before coating the graphene layer, the preparation method of the graphene-copper composite wire further includes: The surface of the graphene-copper composite wire core is polished.
15. A winding, characterized in that, The graphene copper composite wire includes the graphene copper composite wire as described in any one of claims 1 to 10 or the graphene copper composite wire prepared by the method described in any one of claims 11 to 14.